“Toolbox” for the Processing of Functional Polymer Composites - Wei, Yun; Zhou, Hongju; Deng, Hua; Ji, Wenjing; Tian, Ke; Ma, Zhuyu; Zhang, Kaiyi; Fu, Qiang (Nano-Micro Letters, 2021)
Functional polymer composites (FPCs) have attracted increasing attention in recent decades due to their great potential in delivering a wide range of functionalities. These functionalities are largely determined by functional fillers and their network morphology in polymer matrix. In recent years, a large number of studies on morphology control and interfacial modification have been reported, where numerous preparation methods and exciting performance of FPCs have been reported. Despite the fact that these FPCs have many similarities because they are all consisting of functional inorganic fillers and polymer matrices, review on the overall progress of FPCs is still missing, and especially the overall processing strategy for these composites is urgently needed. Herein, a “Toolbox” for the processing of FPCs is proposed to summarize and analyze the overall processing strategies and corresponding morphology evolution for FPCs. From this perspective, the morphological control methods already utilized for various FPCs are systematically reviewed, so that guidelines or even predictions on the processing strategies of various FPCs as well as multi-functional polymer composites could be given. This review should be able to provide interesting insights for the field of FPCs and boost future intelligent design of various FPCs. Highlights: 1 The processing methods of functional polymer composites (FPCs) are systematically summarized in “Toolbox”. 2 The relationship of processing method-structure-property is discussed and the selection and combination of tools in processing among different FPCs are analyzed. 3 A promising prospect is provided regarding the design principle for high performance FPCs for further investigation.